Endonasal Endoscopic Pituitary Adenoma Resection in light of the COVID-19 Pandemic: A Technical Report - Barbosa, Danilo Talacimon; Oberman, Dan Zimelewicz; Moreira, Alick Durão; Borges, Luisa; Gonçalves, Felipe; Cabral, Gustavo Sereno Porto; Barros, Rafael Rego; Vaitsman, Rafael; Sodré, Rodrigo; Kleskoski, João; Maia, Orlando; Correa, Jorge Luis Amorim (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction The endoscopic endonasal transsphenoidal approach (EETA) is routinely used to treat sellar and suprasellar tumors. It provides safe and direct access to tumors in these locations, with wide visualization of anatomical landmarks and great surgical results. With the COVID-19 pandemic, despite the high risk of transmission involved, various surgical procedures cannot be postponed due to their emergency.Case Report A 62-year-old female presented in the previous two months with headaches, followed by bilateral severe visual loss. In 2016, she was submitted to subtotal resection of a non-secretory macroadenoma. Because of the progressive visual deficits, the EETA was used to the resect the pituitary adenoma.Technical Note We developed a low-cost adaptation to the surgical fields, covering the patient's head and superior trunk with a regular surgical microscope bag with a tiny slit to enable the endoscope and surgical instruments to enter the nose, thus protecting the personnel in the operating room from the aerosolization of particles. This makes surgery safer for the surgical team and for the patient.Conclusion In view of the lack of literature on this subject, except for some reports of experiences from some services around the world, we describe the way we have adjusted the EETA in the context of the COVID-19 pandemic.
Keywords: endoscopic; endonasal; transsphenoidal; skull base; neurosurgery